Beyond inflammation: the molecular basis of bone remodeling in axial spondyloarthritis and psoriatic arthritis - Lopalco, Giuseppe; Cito, Andrea; Iannone, Florenzo; Diekhoff, Torsten; Poddubnyy, Denis; Proft, Fabian (Frontiers in Immunology, 2025)
Spondyloarthritis (SpA) encompasses a group of chronic inflammatory diseases with overlapping genetic, clinical, and radiographic features. Axial spondyloarthritis (axSpA), a subset of SpA, predominantly involves the sacroiliac joints and spine, often progressing to ankylosis, severe disability, and functional impairment. Psoriatic arthritis (PsA), another SpA subtype, is characterized by a heterogeneous phenotype that includes peripheral arthritis, enthesitis, and axial involvement, frequently associated with psoriasis. Bone remodeling in axSpA and PsA is driven by a dynamic interplay between inflammatory cytokines and the uncoupling of anabolic and catabolic processes, resulting in bone erosion, systemic and local bone loss, and pathological new bone formation. In axSpA, tumor necrosis factor-alpha (TNFα) and interleukin-17A (IL-17A) drive osteoclastogenesis via the RANKL pathway while suppressing osteoblast-mediated bone formation through WNT/β-catenin signaling. Mechanical stress, combined with inflammatory mediators, promotes mesenchymal stem cell differentiation and new bone formation, which manifests as syndesmophytes and contributes to progressive ankylosis. Conversely, PsA is distinguished by concurrent bone erosion and neoformation, driven by IL-17A, IL-22, and IL- 23, with axial disease exhibiting asymmetrical, bulky para-syndesmophytes rather than the fine, hair-like syndesmophytes typical of axSpA. Advanced imaging modalities, particularly MRI, have elucidated key mechanisms of disease progression, revealing processes such as fat metaplasia and reparative changes. This review explores the intricate molecular and cellular mechanisms underlying bone remodeling in SpA, emphasizing both shared pathways and disease-specific features. It aims to enhance the understanding of these processes to support the development of more precise and effective therapeutic approaches tailored to axSpA and PsA.